Comparison of gas chromatography techniques for the analysis of organochlorine pesticides in sediments. Issue 3 (2nd April 2020) - García, L.; Muro, C.; De La Rosa, I.; Amador-Muñoz, O.; Ponce, M.G.; Borja, M.
ABSTRACT: The response of two chromatography techniques (GC) for electron capture (GC-ECD) and GC-coupled to a mass spectrometer with negative chemical ionization (GC-MS/NCI) was compared to validate the quantification of organochlorine pesticides (OCPs) in certified sedimentary material. Curves linearity, limits of detection, limits of quantification, accuracy, efficiency and precision were used to validate the analytical techniques As result, both GC methods displayed high values of validation parameters, demonstrating an optimal analytical response; however, comparative ANOVA analysis and Fisher test showed significative differences between ECD and MS/NCI.  A high linearity (r) and sensitivity were observed in GC-MS/NCI and ECD; MS/NCI showed around r=0.998-0.99 for the 14 standard OCPs, whereas GC-ECD displayed a range between r=0.983-0.998. Limits of detection and quantification from MS/NCI showed also a high detection of low concentration (0.03 ng/mL) of OCPs compared to ECD (1.2 ng/mL). Accuracy of analysis of OCPs by ECD exhibited a positive bias for the specific analyte's alpha-HCH, aldrin and heptachlor epoxide and in low concentration (1-10 ng/mL); however, MS/NCI showed only positive bias in the analysis of endosulfan I (1-2 ng/mL). Recoveries of OCPs by GC-MS/NCI were higher than those obtained by GC-ECD (82-117%); demonstrating a high precision within the acceptance criterion stipulated ≤20%.